Analysis of New Trends in Online Translations based on Student’s Perspective : Advantages and Disadvantages - Amna, Shally; Christina, Dian; Adha, Annisha Dyuli; Gusta, Wienda (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The use of Online translation (OT) for doing English assignments is now inevitable. Teachers neither can prevent their students to use OT nor can supervise it when all of the learning process has been running online from home to home. Therefore, both teachers and students should bring out the advantages of OT to improve English competence and to reduce the disadvantages of using OT. This study is aimed to investigate the students’ perspectives of using OT for doing English assignments and to describe the advantages and disadvantages of OT. The study is presented in descriptive qualitative design. The data collection instruments are questionnaires and open-ended questions. The participants are 198 students of Information system department, University of Putra Indonesia YPTK Padang. The findings of this study showed that for about 80% of English students depend their English assignments on OT. Based on the EFL students’ perspective, the advantages of using OT are time saver and instant results and the disadvantages of using OT are inaccuracy in the results relate to cultural context, idiom, sentences with metaphor and pragmatic aspects for learning the structure of English language. The study proposes some ideas for teachers to teach their students strategies and guidance for using OT properly and to avoid making mistakes. Key words: Online Translation, English Assignment, Advantages, and Disadvantages, Pragmatics.